Design of Smart Antenna for 5G Network Using Array Synthesis Methods and Leaky LMS Algorithm - Senapati, Anupama; Patro, B. S.; Roy, Jibendu Sekhar (Wireless personal communications, 2023)
5G antenna arrays are being designed to generate a dedicated stream of data for every single user. This results in more capacity and speed over the network along with the least possible latency rate. Depending upon the direction of the user demanding internet access, the beam can be steered in that direction. Meanwhile, the occurrence of side lobes in such systems can be menacing. The smart antenna is a pivotal technology for modern cellular communication. It helps the user’s signal to determine the direction of arrival It also estimates antenna arrays using an adaptive signal processing algorithm that produces a radiation beam for communication. This work presents beamforming for uniform linear smart antenna array using leaky least mean square algorithm and side lobe level reduction using array synthesis methods like Tchebycheff and Taylor distribution. Multiple interferers are considered for the smart antenna. Here, one of the aims is to reduce side lobe levels nearer to the main beam which can enhance more efficient frequency reuse in a cellular network. Side lobe level is reduced up to about 16 dB that enacted for signal-to-noise ratio to 20 dB.